Sejarah Hubungan Yahudi dan Islam - Munawir Haris (LPPM IAIN Sorong, 2016)
Among the monotheistic religions, only the Islamic religion and the Christians can receive a lot of followers. In the historical development of Jewish religion (Judaism) just not more than ethnocentrism nature, until hardly embraced by other nations accept the Jews. For this phenomenon, al-Faruqi uses the term ethnocentric particularism. This character causes the Jews becomes exclusive, claiming themselves as the chosen ones. Monotheism original teachings of the prophet Moses became stuck in a cage ethnocentrism. Monotheism is not possible without universal mission, without linking themselves with adherents of other religions. Talking about the history of the Jewish religion also means talking about the history of the Israel Children. Both are difficult to separate, because the Jews as a religion, is only fully supported by the Israel Children. However, if you talk about the history of the Jewish religion was confined to the religion revealed to Prophet Musa and taught to his people, then history can be separated, so that the beginning of the Jewish religion began in the days of Moses only. Furthermore, talks about Judaism when linked with the history of the Israelites and when associated with Prophet Musa, it is closely associated with Islam. From this aspect, so it can be understood that the discussion about the relationship of Jews and Muslims is very urgent and significant to explore its historical trajectory